Toxic epidermal necrolysis and its impact on physiotherapy management: a case report - J. Schneiderman; H. Van Aswegen; R. Roos (AOSIS, 2010)
The purpose of this paper is to report on the modified physiotherapy intervention  for  toxic  epidermal  necrolysis  (TEN)  in  a 31 year old pregnant human immunodeficiency virus (HIV) seropositive woman  on antiretroviral  therapy.  Physiotherapy  intervention  consisted  of  nebulisation  and  the  active  cycle  of  breathing  technique  in  order to  clear  secretions.  To restore  lung  volumes,  the  active  cycle  of  breath-ing  technique  was  utilized  in  addition  to  positive  expiratory  pressure,  incentive  spirometry  and  positioning. Passive  and  active  exercises and  stretches  were  employed  to  maintain  and  regain  range  of  motion in  affected  limbs.  Following  intervention, positive  changes  were  noted  in  outcome  measures  such  as  secretion clearance, breath sounds and general function. It is concluded that physiotherapy intervention has a role to play in the rehabilitation of patients with TEN.